SNPs associated with cerebrospinal fluid phospho-tau levels influence rate of decline in Alzheimer's disease. - Carlos Cruchaga (PLoS Genetics, 2010)
Alzheimer's Disease (AD) is a complex and multifactorial disease. While large genome-wide association studies have had some success in identifying novel genetic risk factors for AD, case-control studies are less likely to uncover genetic factors that influence progression of disease. An alternative approach to identifying genetic risk for AD is the use of quantitative traits or endophenotypes. The use of endophenotypes has proven to be an effective strategy, implicating genetic risk factors in several diseases, including anemia, osteoporosis and heart disease. In this study we identify a genetic factor associated with the rate of decline in AD patients and present a methodology for identification of other such factors. We have used an established biomarker for AD, cerebrospinal fluid (CSF) tau phosphorylated at threonine 181 (ptau(181)) levels as an endophenotype for AD, identifying a SNP, rs1868402, in the gene encoding the regulatory sub-unit of protein phosphatase B, associated with CSF ptau(181) levels in two independent CSF series (P(combined) = 1.17 x 10(-05)). We show no association of rs1868402 with risk for AD or age at onset, but detected a very significant association with rate of progression of disease that is consistent in two independent series (P(combined) = 1.17 x 10(-05)). Our analyses suggest that genetic variants associated with CSF ptau(181) levels may have a greater impact on rate of progression, while genetic variants such as APOE4, that are associated with CSF Aβ(42) levels influence risk and onset but not the rate of progression. Our results also suggest that drugs that inhibit or decrease tau phosphorylation may slow cognitive decline in individuals with very mild dementia or delay the appearance of memory problems in elderly individuals with low CSF Aβ(42) levels. Finally, we believe genome-wide association studies of CSF tau/ptau(181) levels should identify novel genetic variants which will likely influence rate of progression of AD.